The Influence of Socio-Economic Variables on Environmental Quality in Java Island in 2023: Application of Spatial Dependency Model Regression - Bachtiar, Bayu Aji; Erawanto, Udin (Universitas Islam Balitar, 2025)
Java Island is one of the regions in Indonesia with low environmental quality. The high population and economic activities that do not pay attention to the environment cause environmental damage in districts in Java Island. Environmental damage caused by pollution and waste can spread to other surrounding areas. This study aims to examine the influence of socio-economic factors on environmental pollution in Java Island using a spatial analysis approach. The analysis method used is SEM. The results of the analysis show that the variables of GRDP at Constant Prices for industrial sector, Human Development index (HDI), urbanization rate, and other factors in neighboring districts significantly reduce the quality of the environment in districts. The results of this study are expected to be a reference for the government in carrying out economic development and improving Human Resources (HR) by prioritizing sustainable development